The AI-Driven Smart Supply Chain: Pathways and Challenges to Enhancing Enterprise Operational Efficiency - Saunders, Emily; Zhu, Xu; Wei, Xiangang; Mehta, Rahul; Chew, Jiajia; Wang, Zhiyuan (Journal of Theory and Practice in Economics and Management, 2025)
In recent years, the rapid acceleration of globalization and digital transformation has significantly increased the complexity of modern supply chains. As enterprises operate in increasingly interconnected and volatile environments, they face rising challenges in managing demand fluctuations, logistics disruptions, and supplier uncertainties. These complexities have exposed the limitations of traditional supply chain management models, which often lack the agility and data-driven capabilities required to respond effectively to dynamic market conditions. Amid these challenges, artificial intelligence (AI) has emerged as a transformative force, offering new possibilities for optimizing supply chain operations. Technologies such as machine learning, deep learning, and reinforcement learning are being applied to forecast demand, optimize inventory, improve transportation routing, and enable predictive maintenance. The integration of AI into supply chain systems has the potential to not only enhance operational efficiency but also to support real-time decision-making, risk management, and strategic planning. This research contributes both theoretically and practically to the ongoing discourse on intelligent supply chains. From a theoretical perspective, it bridges the fields of AI and supply chain management by exploring how algorithmic models can be embedded into core supply chain processes. The study addresses a notable gap in academic literature by proposing integrated frameworks that align technical innovations with managerial practices. From a practical standpoint, the research provides actionable insights for enterprises aiming to adopt AI-driven supply chain solutions. It offers a structured pathway for digital transformation, grounded in data analytics, algorithmic modeling, and operational performance metrics. The study seeks to answer three key research questions. First, how can AI technologies be effectively leveraged to optimize critical components of the supply chain? Second, which types of AI algorithms have the most significant impact on improving enterprise operational efficiency? Third, what challenges do organizations encounter when implementing AI systems within their supply chain infrastructures? To address these questions, the research employs a multi-faceted methodology, combining case analysis, data mining, and algorithm modeling. Real-world case studies are examined to understand the adoption patterns and outcomes of AI integration in supply chains. Machine learning and optimization algorithms are utilized to simulate and evaluate different AI applications, while performance indicators such as cost efficiency, response time, and resource utilization are used to assess the effectiveness of these implementations. This methodological approach ensures a comprehensive understanding of both the technical mechanisms and the strategic implications of AI-driven supply chain transformation.